The Root-Associated Microbial Community of the World's Highest Growing Vascular Plants - Angel, Roey; Conrad, Ralf; Dvorsky, Miroslav; Kopecky, Martin; Kotilínek, Milan; Hiiesalu, Inga; Schweingruber, Fritz; Doležal, Jiří (Microbial ecology, 2016)
Upward migration of plants to barren subnival areas is occurring worldwide due to raising ambient temperatures and glacial recession. In summer 2012, the presence of six vascular plants, growing in a single patch, was recorded at an unprecedented elevation of 6150 m.a.s.l. close to the summit of Mount Shukule II in the Western Himalayas (Ladakh, India). Whilst showing multiple signs of stress, all plants have managed to establish stable growth and persist for several years. To learn about the role of microbes in the process of plant upward migration, we analysed the root-associated microbial community of the plants (three individuals from each) using microscopy and tagged amplicon sequencing. No mycorrhizae were found on the roots, implying they are of little importance to the establishment and early growth of the plants. However, all roots were associated with a complex bacterial community, with richness and diversity estimates similar or even higher than the surrounding bare soil. Both soil and root-associated communities were dominated by members of the orders Sphingomonadales and Sphingobacteriales, which are typical for hot desert soils, but were different from communities of temperate subnival soils and typical rhizosphere communities. Despite taxonomic similarity on the order level, the plants harboured a unique set of highly dominant operational taxonomic units which were not found in the bare soil. These bacteria have been likely transported with the dispersing seeds and became part of the root-associated community following germination. The results indicate that developing soils act not only as a source of inoculation to plant roots but also possibly as a sink for plant-associated bacteria.
Keywords: DNA fungální; DNA, Fungal; Upward migration; DNA bakterií; Indie; lipnicovité; Sequence Analysis, DNA; Subnival soil; RNA ribozomální 16S; Vascular plants; Saussurea; RNA, Ribosomal, 16S; biomasa; Brassicaceae; sekvenční analýza DNA; DNA, Bacterial; Plant-associated bacteria; kořeny rostlin; Mycorrhizae; Rhizosphere; půdní mikrobiologie; India; Poaceae; rhizosféra; Bacteria; Biomass; Plant Roots; mykorhiza; Soil Microbiology